Analisa Pemanfaatan Gas Buang Sterilizer Untuk Menghasilkan Energi Listrik Di PT. Tamora Agro Lestari - Sulvan Hardiansyah; Suwitno Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
To increase the production capability of palm oil mills, good technical knowledge is required in the operation of the equipment in the factory. With the aim of getting maximum results, do not ignore quality of the resulting production. The first equipment in a palm oil processing plant is a sterilizer. Sterilizer is a pressurized vessel used to boil palm oil. Sterilizer uses steam as a heating medium derived from a steam turbine. After the fruit stew process is complete, then the residual steam from the sterilizer can be used to produce electrical energy so that the remaining boiled steam is not wasted into the environment. The result of study obtained to energy value of high pressure turbine is work 1233.93 KW, the low pressure turbine is work 1389.36 KW. Thermal efficiency of high pressure turbine 48.64%, and thermal efficiency of low pressure turbine 54.84%. From the utilization of flue gas, thermal efficiency increases 6.2%. Keywords: Sterilizer, Steam Turbine, Rankine Cycle.